Peptide-based nano-antibiotic transformers with antibiotic adjuvant effect for multidrug resistant bacterial pneumonia therapy. (June 2022) - Liu, Jiao; Zhang, Xiao; Zou, Pengfei; Yao, Jiahui; Liu, Lingling; Cai, Yun; Sun, Tongyi; Gao, Yuanyuan; Li, Li-Li
Abstract: Antibiotic-resistance is a growing threat since it endangers the antibiotic treatments such as surgery, transplants and skin damage, which may cause the top-risk of death to public in 2050. Here, we fabricated nano-antibiotic transformers (NATs ) that co-assembled with two lipopeptides and loaded with antibiotics. Once specifically bonding onto the bacterial membrane through multi-targeting of Lipo-20, our NATs activated the in-situ nanofiber deformation, which enhanced membrane disruption and antibiotic penetration resulting in antibiotic adjuvant effect (FICI=0.3, 8-fold reduced the MIC of antibiotic). Meanwhile, the transformed nanofiber further trapped the bacteria similar as the neutrophil extracellular traps (NETs) to enhance the clearance of bacteria in vivo . Additionally, the optimized ratios of two components of lipopeptides maintained the high antibiotic adjuvant activity and more significantly reduced hemolysis. Our NATs significantly prolong the life-time of antibiotic without resistance appear over one month. Finally, the clinical isolated antibiotic-resistance Klebsiella pneumoniae induced pneumonia can be cured based on the synergistic interactions of antibiotic adjuvant activity and targeted antibiotic delivery. We believed such nanotranformers will offer us a broadly applicable drug-delivery system for antibiotic-resistance infection in vivo . Graphical Abstract: Nano-antibiotic transformers (NATs ) can highly specific recognized bacteria and sequently induced deformation to release antibiotics. The nanofibers transformation of NATs endowed antibiotic adjuvant effect and bacterial trapping behavior for synergetic enhanced antibacterial activity. ga1 Highlights: Nano-antibiotic transformers strengthen the therapeutic of resistance pneumonia based on antibiotic-adjuvant-effect. NATs increased antibiotic delivery and enhanced bacterial killing based on antibiotic adjuvant effect. NATs specific recognized bacterial membrane and sequently induced in situ nanofibril structure deformation. The nanofibril structures trapped the bacteria cells through multivalence interactions to enhcance to immun clearance.